New insights, recent advances, and current challenges in the biological treatment of multiple myeloma - Vallet, Sonia; Podar, Klaus (Expert opinion on biological therapy, 2013)
Introduction: The availability of thalidomide, lenalidomide, and bortezomib has radically changed multiple myeloma (MM) treatment and significantly improved patients' outcome. Nevertheless, MM is still an incurable disease due to the development of resistance and relapse practically in all patients. Unraveling MM pathogenesis, identifying prognostically high-risk patient populations, and optimizing current treatment strategies are among the challenges we are facing to reach a cure for this disease. Areas covered: This article reviews recent advances of the genomic analysis of malignant plasma cells and summarizes new insights into the pathophysiologic role of the MM microenvironment and the clinical assessment of derived novel therapeutic strategies. Moreover, current efforts to improve risk stratification and drug development are discussed, and most recent results of Phase II and III clinical trials that aim to optimize existing treatment regimens and to assess the next-generation anti-MM strategies are discussed. A systematic search was conducted of the Pubmed Medline, Embase, and Cochrane Library databases for primary articles, as well as of conference abstracts (e.g., of the American Society of Hematology, the American Society of Clinical Oncology, the American Association of Cancer Research, the European Hematology Association, and the Multiple Myeloma Workshop 2013), practice guidelines, and registries of clinical trials. Expert opinion: Given continuing advances to overcome current treatment challenges in MM, we are confident that long-lasting responses can be expected in many of our patients within the next decade.